Long-Term Effects on Volume Change in Musculocutaneous Flaps after Head and Neck Reconstruction - Sakakibara, Akiko; Kusumoto, Junya; Sakakibara, Shunsuke; Hasegawa, Takumi; Akashi, Masaya; Minamikawa, Tsutomu; Furudoi, Shungo; Hashikawa, Kazunobu; Komori, Takahide (Journal of Reconstructive Microsurgery, 2019)
Objective Musculocutaneous flap reconstruction surgery is one of the standard procedures following head and neck cancer resection. However, no previous studies have classified flaps in terms of muscle and fat or examined them after long-term follow-up. The purpose of this study was to estimate the fat and muscle volume changes in musculocutaneous flaps during long-term follow-up.Methods We conducted a retrospective analysis of 35 patients after musculocutaneous flap reconstruction. The total, fat, and muscle volumes of the musculocutaneous flaps were measured using 3-dimensional images. Changes in flap volumes over time (1 month, 1 year [POY1], and 5 years [POY5] postoperatively) were assessed. Flap persistence was calculated using flap volumes at 1 month after reconstruction for reference.Results Flap persistence at POY5 was 42.0% in total, 64.1% in fat, and 25.4% in muscle. Muscle persistence was significantly decreased (p < 0.0001). In a multiple regression analysis, decreased body mass index (BMI) of ≥ 5% influenced fat persistence less than muscle persistence at POY1; however, there was no significant difference at POY5. Postoperative radiation therapy was associated with a significant decrease in total flap persistence at POY1 (p = 0.046) and POY5 (p = 0.0097). Muscle persistence significantly decreased at POY5 (p = 0.0108). Age significantly influenced muscle volume at POY1 (p = 0.0072).Conclusion Reconstruction flaps are well-preserved with high fat-to-muscle ratios. Recommendations for weight maintenance are necessary for patients less than 2 years after surgery due to the influence of BMI on fat persistence. Radiation therapy is necessary for some patients based on their disease state. Intensity-modulated radiation therapy can be offered to reduce scattering irradiation to normal tissues.
Keywords: head and neck reconstruction; musculocutaneous flap; flap atrophy; flap persistence; BMI; radiation therapy